Inflammation-based Scores are Associated with the Prognosis of Patients with Aneurysmal Subarachnoid Hemorrhage After Neuro-intervention - Yi, Ho J.; Lee, Dong Hoon; Sung, Jae Hoon (Current Neurovascular Research, 2020)
Objective: Prognostic significance of inflammatory response has been reported in various diseases. The objective of this study was to analyze the association between inflammation- based scores and the prognosis of patients who underwent neuro-intervention for aneurysmal subarachnoid hemorrhage (SAH). Methods: Inflammation-based scores such as neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), and monocyte to high-density lipoprotein cholesterol (HDL-C) ratio (MHR) were analyzed for aneurysmal SAH patients who underwent endovascular intervention. Unfavorable functional outcome was defined as a modified Rankin Scale (mRS) score of 3-6. Receiver operating characteristic (ROC) curve analysis was performed to identify cut-off values of inflammation- based scores for predicting unfavorable functional outcome. Logistic regression analyses were performed to explore the relationship between inflammation-based scores and the prognosis of patients. Results: A total of 498 patients were enrolled. Optimal cutoff values of inflammation-based scores of NLR, LMR, and MHR for unfavorable functional outcome were 5.7, 4.2, and 1.5, respectively (p < 0.001, < 0.001, and 0.004, respectively). In multivariate analysis, NLR value ≥ 5.7 (odds ratio [OR] 1.92, 95% CI 1.42-3.42; P = 0.008), LMR value < 4.2 (OR 1.74, 95% CI 1.48-2.98; P = 0.018), and MHR value ≥ 1.5 (OR 1.44, 95% CI 1.22-2.82; P = 0.040) were independently associated with unfavorable functional outcome. Conclusion: Inflammation based scores were associated with functional outcome after endovascular intervention for aneurysmal SAH. Higher NLR and MHR with lower LMR could predict unfavorable outcomes of aneurysmal SAH patients who underwent endovascular intervention.
Keywords: inflammation